The Impact of Service Quality on Customer Loyalty in Government Banks in Nepal - Dahal, Bhushan (KIC International Journal of Social Science and Management, 2022)
Service Quality is the strategic tool to reinforce competitive advantage and increased profitability in business. The Service Sector, including Banks, is using this strategic component to attract and retain customers, as they have to provide service carefully because of the availability of banks. This study aims to examine the relationship between service quality and customer loyalty in public banks in Nepal. A SERVQUAL model evaluates and identifies service quality dimensions that impact customer loyalty. During the research, questionnaires were sent out to customers, and 316 valid responses were recorded from public banks in Kathmandu. We conducted regression and correlation analyses on the collected data to test some hypotheses. After analyzing the data, we concluded that reliability, responsiveness, and empathy significantly impact customer loyalty. In contrast, tangibility and assurance have insignificant relation to customer loyalty in the public banking sector of Nepal. The finding of this study will add significant wisdom to policymakers of both public and private banks of Nepal and Asia to develop strategies to get a competitive advantage.